Migration is a strategy choosen by fishermen as a way out from their poverty: Many fishermen live in Muara Angke come from outside Jakarta. The objectives of the research are to identify characteristic of fisherman who migrate to Muara Angke and factors influence the fisherman to migrate to Muara Angke. The method use in this research is a case study and analyzed by descriptive and non parametric statistic. The research showed that push migration factor was decreasing of fish yield caused by ove - Pantas Angelia; Anna Fatchiya; Istiqlaliyah Muflikhati (Buletin Ekonomi Perikanan, 2006)
Migration is a strategy choosen by fishermen as a way out from their poverty: Many fishermen live in Muara Angke come from outside Jakarta. The objectives of the research are to identify characteristic of fisherman who migrate to Muara Angke and factors influence the fisherman to migrate to Muara Angke. The method use in this research is a case study and analyzed by descriptive and non parametric statistic. The research showed that push migration factor was decreasing of fish yield caused by over fishing which bring iI.,.,act to deaeasing as their income. And the pull migration factors were so many work opportunities, bustling town, and the many facilities could be accessed by them including fish marketing matter in destination area.